FUNGSI SURAT PERSETUJUAN PASIEN ATAS TERAPEUTIK MEDIK (PTM) DOKTER - Ari Purwadi; Harry Kurniawan Gondo (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2007)
Relation between doctor with patient have happened since ahead ( ancient Greek era), doctor as a giving medication to one who require it. This relation represent very personal based of trust of patient to doctor. Relation between doctor with this patient early from vertical relation pattern which starting from principle